Probabilistic Top-k query processing in distributed sensor networks - Mao Ye; Xingjie Liu; Wang-Chien Lee; Dik Lun Lee (2010 IEEE 26th International Conference on Data Engineering (ICDE 2010), 2010)
In this paper, we propose the notion of sufficient set for distributed processing of probabilistic Top-k queries in cluster-based wireless sensor networks. Through the derivation of sufficient boundary, we show that data items ranked lower than sufficient boundary are not required for answering the probabilistic top-k queries, thus are subject to local pruning. Accordingly, we develop the sufficient set-based (SSB) algorithm for inter-cluster query processing. Experimental results show that the proposed algorithm reduces data transmissions significantly.